2023
DOI: 10.1073/pnas.2211091120
|View full text |Cite
|
Sign up to set email alerts
|

Effective bet-hedging through growth rate dependent stability

Abstract: Microbes in the wild face highly variable and unpredictable environments and are naturally selected for their average growth rate across environments. Apart from using sensory regulatory systems to adapt in a targeted manner to changing environments, microbes employ bet-hedging strategies where cells in an isogenic population switch stochastically between alternative phenotypes. Yet, bet-hedging suffers from a fundamental trade-off: Increasing the phenotype-switching rate increases the rate at which maladapted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Thus, by transiently increasing the number of division events, a bacterial population will temporarily exhibit a broader range of phenotypes. Phenotypic heterogeneity increases in adverse environments in both prokaryotic and eukaryotic populations, and previous work has shown that heterogeneity promotes adaptation to time-varying stress by facilitating development of resistance-conferring mutations, alleviating the fitness cost of constitutive expression of unnecessary proteins, and/or allowing for exploration of new phenotypes better suited for the harsher environment 56 60 . These results suggest that bacterial cells utilize division control to increase population heterogeneity in response to harsh environmental perturbations, thus facilitating adaptation to new environments and conferring increased population fitness in time-varying environments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by transiently increasing the number of division events, a bacterial population will temporarily exhibit a broader range of phenotypes. Phenotypic heterogeneity increases in adverse environments in both prokaryotic and eukaryotic populations, and previous work has shown that heterogeneity promotes adaptation to time-varying stress by facilitating development of resistance-conferring mutations, alleviating the fitness cost of constitutive expression of unnecessary proteins, and/or allowing for exploration of new phenotypes better suited for the harsher environment 56 60 . These results suggest that bacterial cells utilize division control to increase population heterogeneity in response to harsh environmental perturbations, thus facilitating adaptation to new environments and conferring increased population fitness in time-varying environments.…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlights that even highly inbred, de facto homozygous genetic backgrounds maintain a physiologically relevant reservoir of phenotypic variation, which can be exposed by stress. While stress often increases phenotypic variation in isogenic and inbred populations (Thattai & van Oudenaarden, 2004; Newman et al ., 2006; Braendle & Félix, 2008; Tokatlidis et al ., 2010; Uyttewaal et al ., 2012; Holland et al ., 2013; Mitosch et al ., 2017; Sandner et al ., 2021; de Groot et al ., 2023), phenotypic robustness (i.e. low nongenetic variation) is associated with stress tolerance and vigor in crops and lifestock (Tollenaar & Lee, 2002; Blasco et al ., 2017; Elgersma et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Stresses encountered by yeast range from infrequent stresses, such as NaCl, seldom encountered by yeast populations in Nature and highly toxic to them [31][32][33] , to ecologically relevant stresses that often perturb yeast populations, such as pH or temperature fluctuations. It is possible that the first mode of adaptation we observed, in which all cells take on the same solutions and obtain similar fitness, is employed when an unfamiliar stress is encountered 34,35 . On the other hand, when assaulted with familiar stress, the cell has a comprehensive arsenal of proteins 36 whose expression can be modified at its disposal, resulting in multiple, distinct, single-cell events, each with its own fitness 37 .…”
Section: Discussionmentioning
confidence: 99%